Bat‐borne viruses in Africa: a critical review. (18th February 2020) - Markotter, W.; Coertse, J.; De Vries, L.; Geldenhuys, M.; Mortlock, M.
Abstract: In Africa, bat‐borne zoonoses emerged in the past few decades resulting in large outbreaks or just sporadic spillovers. In addition, hundreds of more viruses are described without any information on zoonotic potential. We discuss important characteristics of bats including bat biology, evolution, distribution and ecology that not only make them unique among most mammals but also contribute to their potential as viral reservoirs. The detection of a virus in bats does not imply that spillover will occur and several biological, ecological and anthropogenic factors play a role in such an event. We summarize and critically analyse the current knowledge on African bats as reservoirs for corona‐, filo‐, paramyxo‐ and lyssaviruses. We highlight that important information on epidemiology, bat biology and ecology is often not available to make informed decisions on zoonotic spillover potential. Even if knowledge gaps exist, it is still important to recognize the role of bats in zoonotic disease outbreaks and implement mitigation strategies to prevent exposure to infectious agents including working safely with bats. Equally important is the crucial role of bats in various ecosystem services. This necessitates a multidisciplinary One Health approach to close knowledge gaps and ensure the development of responsible mitigation strategies to not only minimize risk of infection but also ensure conservation of the species. Abstract : Hundreds of viruses have been described from bats in Africa, some with proven spillover and causing human deaths, however for the majority there is no information on spillover potential. We summarize and critically analyze the current knowledge on African bats as reservoirs for corona, filo, paramyxo and lyssaviruses, including important characteristics of bats like biology, evolution, distribution and ecology that not only make them unique amongst most mammals but also contribute to their potential as viral reservoirs. We highlight the gaps in knowledge that is often not available to make informed decisions on zoonotic spillover potential. Despite this it is still important to recognize the role of bats in zoonotic disease outbreaks and implement mitigation strategies to prevent exposure to infectious agents, including working safely with bats. Equally important is the crucial role of bats in various ecosystem services.